Ecología comunitaria de los gasterópodos marinos (Mollusca: Gastropoda) en Isla Contoy, México - Cruz-Abrego, Flor Marina (1994)
Marine gastropods collected in Contoy Island, Caribbean of Mexico, inclnde 863 individuals in 24 families, 34 genera and 27 species. Characteristic families were Columbellidae, Phasianellidae, Caecidae and Marginellidae, and most species belonged to Tricolia, Caecum and Marginella. Crepidula maculosa, Tricolia thalassicola and Marginella lavalleana are representative for the zone. Most animals were collected alive (86%). Camivorous (40%) and herbivorous (36%) species were lhe dominant feeding guilds; 71 % of the species live in eurihaline waters; 29% are polyhaline and eurihaline. Epifaunal gastropods (76%) dominate over seminfaunal (20%) and infaunal (4%) species. The general distribution of the species in the West Tropical Atlantic is reviewed. Zoogeographically eighteen species are Caribbean and 21 Antillean. Twenty one are new records for the Island. The Yucatan current seems to be an important factor in gastropod distribution.